2012
DOI: 10.4236/health.2012.47067
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effects of a synthetic Aluminium-Magnesium Silicate, on Avian Influenza Virus

Abstract: Effects a synthetic Aluminium-Magnesium Silicate [AMS] has on Avian Influenza Virus (AIV) were tested. Equal amounts of AIV samples and of the AMS were mixed, kept one hour at room temperature before centrifuging. The supernatants were remeasured and tested for, viral titre, Mean Death Time (MDT) and Mortality Rate of chicken Embryos (EMR). Volumes of the viral samples reduced at rate of 23.4% ± 5.48%. Viral titres reduced significantly (P < 0.01) from HA, 73 ± 32.72 to 1.4 ± 0.43. Also, EMR of infected chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…This result agrees with earlier results got with use of the AMS on Peste des Petits Ruminants Virus [24], Infectious Bursa Disease virus [16], Canine parvovirus [17], Egg Drop Syndrome Virus [25], Newcastle disease Virus [18] and Avian Influenza virus [26]. Chenicoff and Venkatachrisnan [8] reported that Aluminum-Magnesium Silicate molecules poss both positive and negative electrically charged ends.…”
Section: Discussionsupporting
confidence: 83%
“…This result agrees with earlier results got with use of the AMS on Peste des Petits Ruminants Virus [24], Infectious Bursa Disease virus [16], Canine parvovirus [17], Egg Drop Syndrome Virus [25], Newcastle disease Virus [18] and Avian Influenza virus [26]. Chenicoff and Venkatachrisnan [8] reported that Aluminum-Magnesium Silicate molecules poss both positive and negative electrically charged ends.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the following measures should be provided. (1) Some practical solutions to reduce shedding of the viruses by treating the wild birds via using antiviral drugs (Ezeibe et al, 2011;Ezeibe et al, 2012) during migration time.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Therefore, the following measures should be provided. (1) Some practical solutions to reduce shedding of the viruses by treating the wild birds via using antiviral drugs (Ezeibe et al., 2011; Ezeibe et al., 2012) during migration time. (2) Establishment of a water birds' census centre in the region to provide all the necessary information on water birds and the passive surveillances.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Studies have shown that the AMS has antiviral effects against all seven viruses so far tested [18][19][20][21][22][23][24]. Since net electrical charge of HIV is positive, while those on AMS platelets are negative [10,12], AMS may have antiretroviral effects.…”
Section: Introductionmentioning
confidence: 99%